Differentiated Learning Through Photo Media to Enhance Writing Skills of Recount Texts in English for Junior High School Students - Romadhon, Amin Fauzy; Fauzy, Moch. Amirul; Mulyadi, Achmad; Muhajir, Muhajir; Haerussaleh, Haerussaleh (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
English language learning in class VIII-B is still perceived as suboptimal, as evidenced by the number of students who are unable to write recount texts accurately. The researcher implemented differentiated learning focused on content for the students. The research aimed to determine how to improve students’ ability to write recount texts through photo media in class VIII-B. The research design included two cycles: Cycle 1 and Cycle 2. The data type used was quantitative, examining in-depth the results of writing recount texts using photo media, drawing conclusions from students’ learning outcomes, observing activities, and collecting responses from students. The students’ learning outcomes in Cycle 1 were 12.0%, with 3 students completing the task and 22 students (88.0%) not completing it. In Cycle 2, 14 students (56.0%) completed the task, indicating a significant improvement due to the use of photo media. Therefore, it can be concluded that differentiated learning through photo media is highly effective in enhancing recount text writing skills, leading to an interactive and creative classroom.